2015
DOI: 10.1590/0102-311x00065314
|View full text |Cite
|
Sign up to set email alerts
|

Disparidades en salud mental asociadas a la orientación sexual en adolescentes mexicanos

Abstract: El objetivo de este estudio fue documentar las disparidades en salud mental relacionadas con la discriminación por orientación sexual en adolescentes de México. Se estudió una muestra nacional representativa de estudiantes de bachillerato. Se usaron dos indicadores de orientación homosexual: haber tenido un novio del mismo sexo y haber tenido relaciones sexuales con alguien del mismo sexo. Los eventos fueron: depresión, autoestima, ideación suicida e intento de suicidio y consumo de cigarros, alcohol y otras d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
4
0
4
Order By: Relevance
“…Many families, faced with the dissidence of the heterosexuality of their members, carry out a series of punishments, ranging from mild verbal offenses to serious physical violence (24) . Studies show that rejection and family violence in the outcoming process and the non-provision of social support have a direct impact on the health of homosexual adolescents and young people, with consequences such as: social isolation, depression, suicidal ideation and attempt, low performance low self-esteem, higher social exposures and an increase in internalized homophobia (1)(2)(25)(26) . Data from a survey of ten women living heterosexual-normative dissenting lifestyles with a focus on homophobia in the family context revealed that families exert control over their members in order to maintain the compulsion of heterosexuality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many families, faced with the dissidence of the heterosexuality of their members, carry out a series of punishments, ranging from mild verbal offenses to serious physical violence (24) . Studies show that rejection and family violence in the outcoming process and the non-provision of social support have a direct impact on the health of homosexual adolescents and young people, with consequences such as: social isolation, depression, suicidal ideation and attempt, low performance low self-esteem, higher social exposures and an increase in internalized homophobia (1)(2)(25)(26) . Data from a survey of ten women living heterosexual-normative dissenting lifestyles with a focus on homophobia in the family context revealed that families exert control over their members in order to maintain the compulsion of heterosexuality.…”
Section: Discussionmentioning
confidence: 99%
“…International studies show that how the family reacts to the disclosure of sexual orientation influences the quality of life and health of gays and lesbians, for example, negative reactions of family members are associated with lower social support and higher incidence of health problems such as anxiety, depression, suicidal ideation, and excessive alcohol consumption (1)(2)(3) . It is not, therefore, a process restricted to the individual field of people, but it involves the collectivity and, consequently, the professionals and health services that serve the LGBT population.…”
mentioning
confidence: 99%
“…On the other hand, several recent studies demonstrate that there is an inverse relation between suicidal behavior and family protection factors as support, cohesion and adaptation in the family on moments of crisis (5)(6)(7)(8) , also involving suicide attempts among children constantly exposed to family conflicts that could be prevented or addressed appropriately (9) . This signals the importance of greater preventive efforts whereas families as context of attention and care (5) , since this type of death causes intense mental suffering for the family, and can increase their own predisposition to suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, existen especializados en la magnitud ade-- 15 pues se espera poco error de medición en una evaluación que servirá para la toma de decisiones. Asimismo, el número de ítems y el tamaño muestral impactan sobre la 16 así como 17 Cabe un índice de consistencia interna, 18 só El segundo aspecto está referido por el error muestral, su parámetro puede variar en alguna magnitud.…”
unclassified
“…15,16 Un estudio cuyo objetivo fue documentar las disparidades en salud mental relacionadas con la discriminación por orientación sexual en adolescentes de México indicó entre sus hallazgos que los eventos de depresión, autoestima, ideación suicida e intento de suicidio y consumo de cigarros, alcohol y otras drogas en los sujetos de estudio, se diferenciaban con la experiencia de violencia en la familia y la escuela. 17 No basta con establecer marcos legales para avanzar en el plano de los derechos humanos; se debe trabajar a través de planes de acción integrales que visualicen espacios articuladores para la familia y la política pública, como lo es la escuela.…”
unclassified